Observation of quantum vortex core fractionalization and skyrmion formation in a superconductor - Yu Zheng; Quanxin Hu; Xin Yu; Haijiao Ji; Igor Timoshuk; Julien Garaud; Hanxiang Xu; Yongwei Li; Ye Gao; Xingye Lu; Vadim Grinenko; Egor Babaev; et al. (Science, 2026)
Magnetic fields can penetrate a superconductor in the form of quantum vortices, which consist of a core singularity with circulating currents. London’s quantization implies that there is one core singularity per quantum of magnetic flux in single-component superconductors. In this study, we report signatures of quantum vortex core fractionalization on the potassium-terminated surface of a multiband superconductor, KFe 2 As 2 . The observed splitting of single integer–flux vortices into several fractional vortices results in a disparity between the numbers of flux quanta and vortex cores. These fractional vortices often arrange in chains, which calculations show are characterized by a ℂP 2 skyrmionic topological invariant; this constitutes a different type of topological defect: the chiral skyrmion. The disparate natures of integer and fractional vortices comprising skyrmions lead to distinct spectroscopic signatures.